Evaluation of the Influence of Organizational Factors, Human Resources, and Entrepreneurship on Agribusiness Business Productivity: A Case Study on Oil Palm Plantations in Cikidang Area, Sukabumi Regency - Judijanto, Loso (Westscience Press, 2023)
This research investigates the impact of organizational factors, human resources practices, and entrepreneurship on agribusiness productivity in the oil palm plantation industry within the Cikidang Area, Sukabumi District. Utilizing a quantitative research design, the study encompasses a comprehensive survey of 121 oil palm plantations, employing descriptive statistics, correlation analysis, and multiple regression analysis with SPSS version 26. The findings reveal a moderate level of organizational efficiency, human resources practices, and entrepreneurial activities. Positive correlations between these factors and agribusiness productivity underscore their interconnected influence. The regression analysis confirms the significant and unique contributions of organizational factors, human resources practices, and entrepreneurship to overall productivity. The study concludes with recommendations for enhancing agribusiness practices and emphasizes the importance of a holistic approach to organizational development, workforce investment, and entrepreneurial initiatives in the pursuit of sustainable and competitive oil palm plantations.